(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
Тoday’s realities set higher education institutions of the physical culture profile to train competitive specialists who can adapt to changing working conditions, capable of professional mobility, who have mastered a high level of theoretical knowledge and practical skills and correspond to the level of highly qualified specialists of the European model. The article substantiates the importance of professional mobility, which requires the modernization of higher physical education and directing it to the training of highly professional specialists in the field of physical education and sports.Formation of professional mobility of future physical culture specialists is a set of principles, methods and means used in the training process to develop in future specialists the ability for constant professional growth, adaptation to changes and readiness for new challenges in the field of physical culture and sports. In the presented research, we found out that the formation of the professional mobility of specialists is a complex and multifaceted process that requires a systematic approach and the involvement of various means and methods of training. Practice-oriented training is an integral part of the training of physical culture specialists, it contributes to the formation of highly qualified specialists ready to work in a dynamic sports environment, thanks to practical experience, graduates have more chances for a successful career and professional growth. This type of training is closely related to professional mobility, forms a creative specialist who makes decisions independently, knows how to analyze situations, apply the acquired knowledge in practice, is capable of new challenges in the field of physical culture and sports. In this study, we identified and characterized the components of professional mobility (motivational, cognitive, activity, reflexive) and presented a clear rationale for the need for their application. We have developed pedagogical conditions, their implementation will allow us to train specialists who will be able to work successfully in the dynamic environment of modern sports. We have justified the fact that when implementing the methodological principles, it is necessary to include disciplines aimed at the development of professional mobility in educational programs (for example, "Innovative technologies in sports", "Sports psychology", "Management in sports"). In practical training, we recommend organizing industrial pedagogical practices, internships, workshops that allow students to gain work experience in different conditions. A mandatory element in the training of physical culture specialists is scientific research activity, which includes the involvement of students in conducting scientific research, writing articles, participating in conferences, and speaking at round tables. The creation of a mentoring system will allow young coaches to receive support from experienced colleagues and organize an active professional community of coaches to share experience, support, exchange ideas and new coaching methods.